The influence of service quality, price perception and customer relationship management on customer satisfaction: The mediating role of trust in early care animal clinics - Mirjawal, Mirjawal; Waluyo, Tri (Keynesia : International Journal of Economy and Business, 2025)
Customer satisfaction has become a major factor in the success of a business organization. However, how customer satisfaction is achieved in the context of veterinary clinics has not been fully studied in the literature. Therefore, this study aims to analyze the effect of service quality, price perception and customer relationship management on customer satisfaction with trust as a mediator at Awal Care Animal Clinic. This study uses a quantitative method with an associative approach. By using a purposive sampling technique, 100 customers of this clinic were taken as data using a questionnaire and then processed using Partial Least Square-Structural Equational Modeling (PLS-SEM). The results of the study indicate that service quality, price perception, Customer relationship management, and customer trust have a positive and significant effect on customer satisfaction. Meanwhile, for indirect relationships, customer trust only mediates the relationship between customer relationship management and customer satisfaction, and does not mediate the relationship between service quality-customer satisfaction and price perception-customer satisfaction.